Design And Fabrication Of Multipurpose Smart Phantom For Positron Emission Tomography/Computed Tomography Imaging [RC78.7.D53 R138 2008 f rb]. - Zainon, Rafidah (2008)
Phantom studies are an important part in medical imaging as it can evaluate the performance and quality assurance (QA) test of dual-modality PET/CT.